Highly Flame Retardant Melamine‐Formaldehyde Cross‐Linked Cellulose Nanofibrils/Sodium Montmorillonite Aerogels with Improved Mechanical Properties. Issue 10 (16th August 2018) - Wang, Liang; Cui, Lingyan; Sánchez‐Soto, Miguel; Shou, Wan; Xia, Zhaopeng; Liu, Yong
Abstract: A facile cross‐linking strategy to construct flame retardant cellulose nanofibril (CNF)/sodium montmorillonite (MMT) aerogels with improved mechanical properties, by incorporating melamine‐formaldehyde (MF) resins into precursor suspensions followed by a freeze‐drying process, is reported in this work. Scanning electron microscopy images indicate that MF cross‐linking does not significantly change the microstructures of CNF and CNF/MMT aerogels. However, the cross‐linking improves the materials' mechanical and flame properties. By incorporating 50 wt% of MF, the compression moduli and compressive stress of CNF aerogels increase by 316% and 114%, respectively. The limiting oxygen index (LOI) value of CNF aerogels also increases from 17.1% to 23.4%. Further addition of MMT increases the CNF aerogels' LOI value to 57% and increases the maximum decomposition temperature by nearly 20 °C. This occurs because MMT and MF induce a synergistic effect which improves the flame retardant properties of the CNFs aerogels. In CNF/MMT composite aerogels, the introduction of 34 wt% of MF leads to a 54.6% reduction of the peak of heat release rate and a 53.2% decrease in total heat release. CNF aerogels made from sustainable feedstocks with excellent mechanical properties and high flame retardancy, like those discussed herein, show promise as fire resistant biofoams. Abstract : A facile method is proposed to fabricate nonflammable cellulose nanofibril (CNF)/sodium montmorillonite composite aerogels with improved mechanical properties by cross‐linking with melamine‐formaldehyde. Montmorillonite and melamine‐formaldehyde have a synergistic effect on the improvement of flame retardancy and mechanical properties of the CNFs aerogels. The modified cellulose nanofibril‐based aerogels have a limiting oxygen value as high as 57%.